Effect of mechanical juice extraction method on the quality of fresh-squeezed apple juice. (January 2020) - Wang, Zhengchen; Cui, Huanyong; Fan, Shichao
Abstract: In order to study the effect of different mechanical juice extraction methods on the quality of fresh-squeezed apple juice, the optimal fresh-squeezed apple juice processing method was selected. The fresh-squeezed apple juice is processed by three kinds of mechanical juice extraction methods: squeezed juice, spiral juicer and broken juice. Five main evaluation indexes of soluble solid content, titratable acid content, value of b*, value of a* and 625nm transmittance of fresh-squeezed apple juice obtained by three mechanical juice extraction methods were determined. Through the analysis and research of the data obtained from the five indicators, the influence of different mechanical juice extraction methods on the quality of fresh-squeezed apple juice was determined, and the mechanical juice extraction method suitable for processing fresh-squeezed apple juice was determined.